2003
DOI: 10.1137/s1064827501392879
|View full text |Cite
|
Sign up to set email alerts
|

Splitting for Dissipative Particle Dynamics

Abstract: Abstract. We study numerical methods for dissipative particle dynamics, a system of stochastic differential equations for simulating particles interacting pairwise according to a soft potential at constant temperature where the total momentum is conserved. We introduce splitting methods and examine the behavior of these methods experimentally. The performance of the methods, particularly temperature control, is compared to the modified velocity Verlet method used in many previous papers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(181 citation statements)
references
References 24 publications
3
176
0
2
Order By: Relevance
“…Dissipative Particle Dynamics, which has become quite popular in the soft-matter community [44][45][46][47][48][49][50][51][52][53][54][55][56], was developed to address the computational limitations of MD. A very soft interparticle potential, representing coarse-grained aggregates of molecules, enables a large time step to be used.…”
Section: Dissipative Particle Dynamics (Dpd)mentioning
confidence: 99%
“…Dissipative Particle Dynamics, which has become quite popular in the soft-matter community [44][45][46][47][48][49][50][51][52][53][54][55][56], was developed to address the computational limitations of MD. A very soft interparticle potential, representing coarse-grained aggregates of molecules, enables a large time step to be used.…”
Section: Dissipative Particle Dynamics (Dpd)mentioning
confidence: 99%
“…-In a recent paper by Nikunen et al [4], the authors present a comparative study of the efficiency of several "novel" DPD integration schemes. The study includes, among others, the Shardlow scheme [6] and also the Lowe scheme [2]. They concluded that the Lowe scheme performs best (but it is not a discretization of the DPD equations).…”
Section: Edp Sciencesmentioning
confidence: 99%
“…Also the irreversible interactions and the conservative interactions are split and treated separately. The method has in common these two features with the Shardlow method [6]. This is different from the usual DPD discretizations where first the contributions of all pair interactions are added and subsequently the update of velocities and positions are computed.…”
Section: Edp Sciencesmentioning
confidence: 99%
“…These concepts have been carried over to the stochastic case by constructing symplectic and quasi-symplectic integrators for stochastic Hamiltonian systems and Langevin equations (see [10,28,29,31,37]). Another branch of splitting approaches in the stochastic field (although not arising from geometric considerations) are splitstep methods, where the stochastic part is separated from the deterministic drift (see [25]).…”
Section: Splitting Methodsmentioning
confidence: 99%